1976
DOI: 10.1079/bjn19760033
|View full text |Cite
|
Sign up to set email alerts
|

Thermic effect of glucose in obese subjects studied by direct and indirect calorimetry

Abstract: I . The thermic effect of a glucose load (50 g) was studied in ten control and eleven obese female subjects, using both direct and indirect calorimetry simultaneously. Experiments were done under conditions of thermal equilibrium (28O and 30 % relative humidity).2. Thermal balance (heat production measured by indirect calorimetry minus heat losses measured directly) was negative in the control group during the fasting period (heat deficit -14.2 _+ 5.0 kJ/m2 per h), whereas that of the obese group was in equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
2
3

Year Published

1982
1982
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(61 citation statements)
references
References 16 publications
5
51
2
3
Order By: Relevance
“…(In the present study the subjects were sitting rather than lying down so that the values obtained for RMR were probably 20-30% higher than the true values of RMR.) Rose & Williams (1961) were also unable to show any difference in the RMR between the large and small eaters in their study. However, it is clear that whereas the RMR comprises the major proportion of energy expenditure in the LEI group, it accounts for less than half the daily energy expenditure of the HE1 group.…”
Section: Ns Ns Nsmentioning
confidence: 89%
See 3 more Smart Citations
“…(In the present study the subjects were sitting rather than lying down so that the values obtained for RMR were probably 20-30% higher than the true values of RMR.) Rose & Williams (1961) were also unable to show any difference in the RMR between the large and small eaters in their study. However, it is clear that whereas the RMR comprises the major proportion of energy expenditure in the LEI group, it accounts for less than half the daily energy expenditure of the HE1 group.…”
Section: Ns Ns Nsmentioning
confidence: 89%
“…Although the LEI group was fatter than the HE1 group, their mean energy intake was less than half that of the HE1 subjects, an illustration of the great diversity of metabolic efficiency that can be observed in man which has been reported on many previous occasions (Widdowson, 1947;Rose & Williams, 1961;Garrow, 1974). This efficiency could not be related to a lower RMR in the LEI group.…”
Section: Ns Ns Nsmentioning
confidence: 91%
See 2 more Smart Citations
“…Further, it should be possible to demonstrate that obese people have a reduced capacity for thermogenesis. Pittet et al (1976) found differences between lean and obese women in the size of response to a small meal (50 g glucose), but this was not confirmed by other workers (Kaplan & Leveille 1976, Clough & Durnin 1970. Blaza (1980) found no differences in the response of five lean and five obese women to a 1000 kcal (4.2 MJ) meal and moderate exercise although there were some differences in response to warm and cool environmental temperatures (all within 20-30"C and described by the subjects as 'comfortable').…”
Section: Adult Manmentioning
confidence: 54%